Plant factory : an indoor vertical farming system for efficient quality food production - Kozai, Toyoki, 1943-; Niu, Genhua; Takagaki, Michiko (Academic Press, an imprint of Elsevier, 2020)
Plant Factory: An Indoor Vertical Faming System of Efficient Quality Food Production presents a comprehensive look at the implementation of plant factory (PF) practices to yield food crops for both improved food security and environmental sustainability. Now in its second edition, the book has been fully revised and updated to include the latest advances in PF technologies. Edited and authored by leading experts in PF and controlled environment agriculture (CEA), the book is divided into four sections, each focused on a key element of successful PF: Section 1: Overview and Concept of Closed Plant Production Systems (CPPS); Section 2: Basics of Physics and PHysiology - Environments and Their Effects; Section 3: System Design, Construction, Cultivation, and Management; and Section 4: Plant Factories in Operation.--COVER.